Robert Southey and the Peninsular War - Packer, Ian; Pratt, Lynda (Palgrave Macmillan, 2018)
This essay examines two aspects of Southey’s Romantic Iberianism that have often been overlooked—his writings on the peninsular conflict in the Edinburgh Annual Register and his unfinished series of inscriptions on the war. Both shed important light on Southey’s developing political ideas and on his sense of his public role. Moreover, they connect Southey the writer of prose (particularly contemporary history) with Southey the controversial Poet Laureate.